The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2010
DOI: 10.1039/c000424c
|View full text |Cite
|
Sign up to set email alerts
|

Investigations of the water clusters of the protected amino acid Ac-Phe-OMe by applying IR/UV double resonance spectroscopy: microsolvation of the backbone

Abstract: In order to investigate the influence of hydration on the backbone of a peptide or protected amino acid, the successive aggregation of water to Ac-Phe-OMe is analysed by means of IR/UV double resonance spectroscopy. To achieve meaningful results the spectra have been recorded in the region of the amide A and OH stretching vibrations as well as the amide I/II modes. Comparison with ab initio and DFT calculations leads to size-selective structural assignments. Two isomers of the mono- and dihydrated clusters and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
74
0

Year Published

2011
2011
2019
2019

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 38 publications
(78 citation statements)
references
References 47 publications
0
74
0
Order By: Relevance
“…This type of experiment on hydrates is, however, difficult to interpret and requires heavy reliance on vibrational spectral data to be successful, at least in terms of an unambiguous assignment. Experimental results beyond a single solvent molecule remain seldom; the interpretation being complicated [55,102,136] by vibrational coupling between solvent molecules.…”
Section: Microsolvation Structures and Complexationmentioning
confidence: 98%
See 2 more Smart Citations
“…This type of experiment on hydrates is, however, difficult to interpret and requires heavy reliance on vibrational spectral data to be successful, at least in terms of an unambiguous assignment. Experimental results beyond a single solvent molecule remain seldom; the interpretation being complicated [55,102,136] by vibrational coupling between solvent molecules.…”
Section: Microsolvation Structures and Complexationmentioning
confidence: 98%
“…Theoretically predicted some time ago [196], experimental illustrations of these effects have been published only quite recently. Several groups have shown that peptides or related flexible molecules undergo a significant structural change upon solvation, as indicated by changes in their H-bonding network [53,55,102,129,136]. One of the most dramatic studies, carried out on a capped amino-acid solvated by one water molecule, documented the effect of microhydration and its dependence on the solvation site occupied by the water molecule for each conformation.…”
Section: Microsolvation Structures and Complexationmentioning
confidence: 98%
See 1 more Smart Citation
“…Useful information can be obtained from experimental gas-phase hydration/solvation studies augmented with theoretical calculations [108][109][110][111][112][113][114][115][116] or specific theoretical calculations for hydrated amino acid side chains, nucleotid base and sugar models [117][118][119][120][121].…”
Section: American Journal Of Modeling and Optimizationmentioning
confidence: 99%
“…With the established scaling factor of 0.9613 [17] the A-type structures show NH vibrations around 3330 cm…”
mentioning
confidence: 99%